2015
DOI: 10.1038/srep10209
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine-induced increase in voluntary activation and strength of the quadriceps muscle during isometric, concentric and eccentric contractions

Abstract: This study investigated effects of caffeine ingestion (8 mg/kg) on maximum voluntary torque (MVT) and voluntary activation of the quadriceps during isometric, concentric and eccentric contractions. Fourteen subjects ingested caffeine and placebo in a randomized, controlled, counterbalanced, double-blind crossover design. Neuromuscular tests were performed before and 1 h after oral caffeine and placebo intake. MVTs were measured and the interpolated twitch technique was applied during isometric, concentric and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
70
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 40 publications
5
70
2
2
Order By: Relevance
“…The mechanism by which caffeine produces ergogenic effects for muscular strength and power activity is not well understood, although it is most likely to involve a supraspinally-driven increase in voluntary muscle activation [4, 13]. For endurance exercise, caffeine elicits performance benefits primarily via adenosine receptor antagonism [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism by which caffeine produces ergogenic effects for muscular strength and power activity is not well understood, although it is most likely to involve a supraspinally-driven increase in voluntary muscle activation [4, 13]. For endurance exercise, caffeine elicits performance benefits primarily via adenosine receptor antagonism [1].…”
Section: Discussionmentioning
confidence: 99%
“…When caffeine supplementation has shown a significant effect on leg muscle strength, this appears primarily in the knee extensors, as opposed to the knee flexors and smaller muscle groups [3]. While initial studies reported the enhancement of peak torque for isometric exercise only [11, 12], recent work has shown a caffeine-induced increase in knee extensor strength regardless of contraction mode [13]. The effect of caffeine intake on power output is unclear [2, 10].…”
Section: Introductionmentioning
confidence: 99%
“…following fatiguing exercise, muscle damage, and training . Moreover, the interpolated twitch technique was applied during dynamic actions of the quadriceps muscle . Since %VA was found to depend on the type of muscle action, the assessment of %VA during dynamic contractions might yield additional information about acute and chronic adaptations in neural drive.…”
Section: Introductionmentioning
confidence: 99%
“…6 Moreover, the interpolated twitch technique was applied during dynamic actions of the quadriceps muscle. [7][8][9][10][11] Since %VA was found to depend on the type of muscle action 12 , the assessment of %VA during dynamic contractions might yield additional information about acute and chronic adaptations in neural drive. Although it has been shown that %VA during isometric contractions can be reliably assessed using single and paired electrical stimuli 13,14 , little is known about the intersession reliability of the interpolated twitch technique applied during dynamic actions of the knee extensor muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations to pain perception following caffeine supplementation have also been reported [31] most likely due to enhanced secretion of β-endorphins [32]. More specifically to strength performance, possible mechanisms also include increased muscle activation [33], motor unit recruitment [34], and enhanced excitation contraction coupling [35].…”
mentioning
confidence: 99%